2021
DOI: 10.3390/agriculture11050381
|View full text |Cite
|
Sign up to set email alerts
|

Grassland Restoration at a Graded Ski Slope: Effects of Propagation Material and Fertilisation on Plant Cover and Vegetation

Abstract: The increasing anthropisation of mountain regions is a cause of soil degradation, which needs to be addressed. Conventional methods of ski slope revegetation often fail to stabilise the soil and recover natural vegetation. To test alternative methods to create a persistent, biodiversity-friendly plant cover, different sowing (site-adapted native propagation materials vs. forage cultivars vs. no sowing) and fertilisation treatments were compared over nine years at a graded ski slope. Because of the gravelly soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Our results indicate that soil spray-seeding not only improves species richness and abundance, but also accelerates seedling growth when compared with artificial seeding and arch columns + planting bags in the Yuanjiang dry-hot valley region, which aligns with studies suggesting that soil spray-seeding is the superior method for vegetation restoration of expressway slopes in semi-humid areas [25,26], and that soil spray-seeding provides a good soil substrate for plant growth and community assembly combining shrubs, flowers, and grass [39][40][41]. Shang et al [42] indicated that natural recovery is a simple and cheap way to increase grass coverage in sub-humid and humid areas, but that was unsuccessful for slope recovery in the dry-hot valley region, probably because (1) seeds on soil surfaces are more vulnerable to animal feeding and sun exposure; (2) steep slopes tend to cause seed loss and soil erosion during the rainy season; (3) climate conditions in the dry-hot valley inhibited the germination and growth of many species; (4) the degraded land lacked seed banks for woody tree species [43][44][45]. Although arch columns + planting bags have produced good results for the restoration of slopes along highways and railway in certain areas [46], they are expensive and unsuitable in the dry-hot valley area.…”
Section: The Effect Of Microbial Fertilizers On Seedling Survival And...mentioning
confidence: 99%
“…Our results indicate that soil spray-seeding not only improves species richness and abundance, but also accelerates seedling growth when compared with artificial seeding and arch columns + planting bags in the Yuanjiang dry-hot valley region, which aligns with studies suggesting that soil spray-seeding is the superior method for vegetation restoration of expressway slopes in semi-humid areas [25,26], and that soil spray-seeding provides a good soil substrate for plant growth and community assembly combining shrubs, flowers, and grass [39][40][41]. Shang et al [42] indicated that natural recovery is a simple and cheap way to increase grass coverage in sub-humid and humid areas, but that was unsuccessful for slope recovery in the dry-hot valley region, probably because (1) seeds on soil surfaces are more vulnerable to animal feeding and sun exposure; (2) steep slopes tend to cause seed loss and soil erosion during the rainy season; (3) climate conditions in the dry-hot valley inhibited the germination and growth of many species; (4) the degraded land lacked seed banks for woody tree species [43][44][45]. Although arch columns + planting bags have produced good results for the restoration of slopes along highways and railway in certain areas [46], they are expensive and unsuitable in the dry-hot valley area.…”
Section: The Effect Of Microbial Fertilizers On Seedling Survival And...mentioning
confidence: 99%
“…While several scientific studies dealing with European Alps was published until the 1990s, a few papers can be found in recent issues (e.g. Hudek et al 2020; Scotton 2021).…”
Section: Introductionmentioning
confidence: 99%